1997
DOI: 10.1136/vr.140.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the causative agent of heartwater (Cowdria ruminantium) from three Amblyomma species in eight Districts of Kenya

Abstract: Thirteen isolates of Cowdria ruminantium were made from eight different Districts of Kenya by four different isolation methods. Feeding adult Amblyomma species ticks derived from nymphs collected in the field and the inoculation of homogenates prepared from adult field ticks had the highest success rate. The reattachment of adult ticks collected in the field was successful on only one of five attempts, and the subinoculation of blood from suspected heartwater carriers was unsuccessful. Seven of the isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The low prevalence of E. ruminantium estimated from the RLB results was surprising, given previous reports of the prevalence of this pathogen in Kenya ( Ngumi et al, 1997 ). To confirm the RLB results, all samples were analyzed with the E. ruminantium -specific qPCR assay based on the pCS20 gene region.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The low prevalence of E. ruminantium estimated from the RLB results was surprising, given previous reports of the prevalence of this pathogen in Kenya ( Ngumi et al, 1997 ). To confirm the RLB results, all samples were analyzed with the E. ruminantium -specific qPCR assay based on the pCS20 gene region.…”
Section: Resultsmentioning
confidence: 61%
“…We also observed a very low prevalence of E. ruminantium , the causative agent of heartwater, by both RLB and the pCS20 qPCR assay . E. ruminantium has previously been isolated in eight districts across Kenya, suggesting that this organism is widely distributed across the country ( Ngumi et al, 1997 ). It is possible that the sequences of the primers and probes used in the RLB assay are not sufficiently similar to those in the corresponding regions in the genomes of the E. ruminantium organisms in the study site to allow for detection.…”
Section: Discussionmentioning
confidence: 99%
“…with a DNA sequence close to E. ruminantium in Moyale Constituency, which is part of the study area in 2016 [ 18 ], and the isolation of the pathogen from Amblyomma spp. in eight districts across Kenya [ 69 ] suggest that there is continuous circulation of E. ruminantium across the country. Since 2016 and during the entire study period in 2020, no clinical heartwater cases were reported from camels, sheep and goats in Marsabit (Boku Bodha, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…evertsi evertsi sampled from livestock in both study locations, though we cannot rule out that this may have come from livestock blood meals. Amblyomma variegatum Fabricius 1794 is the most common and widely distributed Amblyomma tick species of livestock in SSA and is a very important vector of the E. ruminantium in cattle (65). Amblyomma gemma DĂśnitz 1909 sampled from livestock in both study areas was once thought to be less important as a disease vector, but has since been linked with the transmission of a number of pathogens (65, 66).…”
Section: Discussionmentioning
confidence: 99%
“…Pulchellus , and Am. gemma tick pools, all of which have been widely implicated in TBP transmission (65, 66, 83–85). Although all 28 pools of Ar.…”
Section: Discussionmentioning
confidence: 99%